2020
DOI: 10.1016/j.chest.2020.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices for Acute Respiratory Failure and Acute Respiratory Distress Syndrome

Abstract: BACKGROUND: The recent pandemic highlights the essential nature of optimizing the use of invasive mechanical ventilation (IMV) in complex critical care settings. This review of reviews maps evidence-based practices (EBPs) that are associated with better outcomes among adult patients with acute respiratory failure or ARDS on the continuum of care, from intubation to liberation. RESEARCH QUESTION: What EPBs are recommended to reduce the duration of IMV and mortality rate among patients with acute respiratory fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…ARF is often caused by pulmonary and bronchial diseases and ventilatory dysfunction. It mostly occurs in middle-aged and elderly people and poses a serious threat to the life safety of patients [ 16 ]. Affected by a variety of factors, patients with ARF are prone to a series of negative emotions such as anxiety, depression, and tension and produce stress psychological reactions, thereby reducing the patients' treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…ARF is often caused by pulmonary and bronchial diseases and ventilatory dysfunction. It mostly occurs in middle-aged and elderly people and poses a serious threat to the life safety of patients [ 16 ]. Affected by a variety of factors, patients with ARF are prone to a series of negative emotions such as anxiety, depression, and tension and produce stress psychological reactions, thereby reducing the patients' treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged maintenance of the prone position for at least 12 h is associated with significantly reduced mortality in patients with acute respiratory distress syndrome (ARDS) [ 14 ]. Mortality is further reduced when prone positioning is combined with low current volume ventilation and when it is undertaken less than 48 h after the onset of the clinical condition [ 14 – 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…An early mobilization protocol for ARDS patients undergoing invasive mechanical ventilation for more than 24 h resulted in a reduction in total mechanical ventilation time, with reduced frequency of adverse events. There was no significant improvement in mortality or functional status of the patient at discharge [ 14 , 44 , 45 ]. In contrast, it appears that early mobilization does not significantly affect the quality of life of critically ill patients with severe brain damage [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior literature (7) has shown that patients with ARF have improved outcomes in high-volume/high-resource hospitals; however, it does not clarify if the patients have to be initially admitted to a high volume hospital or if they can be transferred from another hospital early in the course of their illness. A matched study of H1N1 patients with acute respiratory distress syndrome in the United Kingdom (45) revealed that patients had improved outcomes when referred to ECMO treatment centers even if they did not end up requiring ECMO, which brings up the question of not only timing of transfer but also early implementation of evidence-based best practices which are more likely to occur in high-volume/high-resource hospitals (46).…”
Section: Discussionmentioning
confidence: 99%